Metal complexes as potential modulators of inflammatory and autoimmune responses. Issue 2 (20th November 2014) - Leung, Chung-Hang; Lin, Sheng; Zhong, Hai-Jing; Ma, Dik-Lung
Abstract : In this perspective, we highlight recent examples in the development of transition metal complexes as modulators of inflammatory and autoimmune responses. Abstract : Over the past few decades, the realm of inorganic medicinal chemistry has been dominated by the study of the anti-cancer properties of transition metal complexes, particularly those based on platinum or ruthenium. However, comparatively less attention has been focused on the development of metal complexes for the treatment of inflammatory or autoimmune diseases. Metal complexes possess a number of advantages that render them as attractive alternatives to organic small molecules for the development of therapeutic agents. In this perspective, we highlight recent examples in the development of transition metal complexes as modulators of inflammatory and autoimmune responses. The studies presented here serve to highlight the potential of transition metal complexes in modulating inflammatory or immune pathways in cells.